SURGICAL CORRECTION OF LONG STANDING 49 YEARS OLD TRAUMATIC ARTERIOVENOUS FISTULA - Muhammad Jamil; Rashid Usman (Journal of University Medical & Dental College, 2015)
ABSTRACT Traumatic arteriovenous ﬁstula (AVF) is the most fascinating and misdiagnosed complication of vascular trauma resulting from an abnormal communication between an artery and a vein. We present a 69 year old retired soldier who suffered a gunshot wound in 1965 war and has developed disparity in limb size which has grown over the years. He complained of pain, varicosities and stasis dermatitis of leg. He was misdiagnosed for years as a case of varicose veins. Clinical diagnosis of traumatic AVF between femoral artery and vein, was made; which was conﬁrmed by Doppler Scan and Computerised Tomography Angiogram (CTA). Open surgical excision of the ﬁstula was done along with venous patchplasty of artery. Patient had an uneventful recovery and was discharged home with monthly follow up for 6 months. We want to highlight the importance of clinical examination and high index of suspicion for traumatic AVF in all those patients who present with venous varicosities and have a history of trauma in past.